(untitled) - Evans, Thomas L. (New York, 2003)
Gilbert Law Summaries are America’s best selling outlines and have set the standard for excellence since they were introduced more than thirty-five years ago. It’s Gilbert’s unique combination of features that makes it the one study aid you’ll turn to for all of your study needs! Walk into class prepared with a comprehensive outline of the law, a concise capsule summary perfect for a quick review before class, charts of every kind, a text correlation chart so that you can match your specific reading assignment to the relevant pages in the Gilbert outline, and an index and table of cases. Ace your final exams with a step-by-step approach to attack your exam, exam tips, and sample multiple choice, true-false, and essay questions
Keywords: Accounting,Financial statements,Lawyers,Luật sư,Kế toán; Standards,Accounting,Kế toán,Tiêu chuấn; United States,United States,Hoa Kỳ